Daily variation of fishing effort and ex-vessel prices in a western Mediterranean multi-species fishery: Implications for sustainable management. (November 2015) - Samy-Kamal, Mohamed; Forcada, Aitor; Sánchez Lizaso, José Luis
Abstract: The daily variation of fishing effort and ex-vessel price was analysed to determine which day of the week is suitable to ban the fishery, as an alternative management measure to the one month seasonal closure. Thus, 10-years landings data were used from two representative trawling ports of the western Mediterranean: Dénia and La Vila Joiosa. Analysis of variance (ANOVA) was used to detect significant differences in fishing effort (total and by métier) and daily ex-vessel price of the main target species. Also, the economic loss produced by banning one day (the proposed measure) was compared to economic loss produced by the seasonal closure (the actual measure). Daily variation in the fishing effort was observed in La Vila Joiosa mainly due to higher effort at the end of the week devoted on crustacean métiers, while effort was similar among days in Dénia. The lowest mean prices for most target species were on Tuesday and Wednesday, and were higher on Monday and Friday. Banning one day per week (Tuesday or Wednesday), when market prices of target species are lower would reduce the double of effort than one month of seasonal closure, and likely without subsidies. However, the loss by banning all Wednesdays (approx. 50 days) was higher in both ports than one month, but lower than an equivalent two months closure. Highlights: Effort variation was due to higher effort at the end of the week devoted on crustacean. Lowest prices were on Tuesday and Wednesday, and higher on Monday and Friday. Banning one day per week would reduce revenues less than a month of closure. Banning one day per week would reduce the double effort than a month of closure.